Extraction and Characterization of Cellulose from Jackfruit Rind (Artocarpus Heterophyllus) / Wahida Abdul Rahman, Noor Aishatun Majid and Siti Fatimah Abd Razak - Abdul Rahman, Wahida; Majid, Noor Aishatun; Abd Rahman, Siti Fatimah (Faculty of Applied Sciences, 2019)
In this study, jackfruit cellulose was extracted by undergoing two steps; bleaching and alkaline treatment. The first step was the production of holocellulose by using bleaching method that removed the lignin from the jackfruit rind (JR). Next step was converting the holocellulose into cellulose by using alkaline treatment at room temperature. The percentage of cellulose extracted from JR in this study was 40% which was higher than the previous research. The characterizations of extracted JR cellulose were investigated by using Fourier Transform Infrared Spectrometer (FTIR) and Scanning Electron Microscopy (SEM). FTIR confirmed that the removal of non-cellulosic components in the jackfruit fibre and the micrograph by SEM displayed a rough surface indicated the presence of the cellulose fibre. Based on this study, JR has the potential to be used as a reinforcement element in composite materials.